2017
DOI: 10.1002/dneu.22552
|View full text |Cite
|
Sign up to set email alerts
|

Advances in noninvasive myelin imaging

Abstract: Myelin is important for the normal development and healthy function of the nervous system. Recent developments in MRI acquisition and tissue modeling aim to provide a better characterization and more specific markers for myelin. This allows for specific monitoring of myelination longitudinally and noninvasively in the healthy brain as well as assessment of treatment and intervention efficacy. Here, we offer a nontechnical review of MRI techniques developed to specifically monitor myelin such as magnetization t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
120
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 134 publications
(185 reference statements)
2
120
0
1
Order By: Relevance
“…In addition to multiple sclerosis (MS) 5 , demyelination is emerging as a prominent cause of disability of many brain diseases including spinal cord injury (SCI) 6 , traumatic brain injury (TBI) 7 , stroke 8 and Alzheimer's disease (AD) 9 . Currently, demyelination can be detected by histopathology, by PET using tracers that bind to myelin such as the amyloid tracer [ 11 C]PiB or [ 11 C]MeDAS 10,11 or by MRI 12,13 . Unfortunately, histopathology is not applicable for in vivo disease monitoring, myelin tracers are not ideal due to binding to multiple targets and the abundance of myelin, and while structural and diffusion MRI offer some insight into the structural integrity of white matter, MRI measurements are not specific to white matter tissue properties such as myelination or fiber density 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to multiple sclerosis (MS) 5 , demyelination is emerging as a prominent cause of disability of many brain diseases including spinal cord injury (SCI) 6 , traumatic brain injury (TBI) 7 , stroke 8 and Alzheimer's disease (AD) 9 . Currently, demyelination can be detected by histopathology, by PET using tracers that bind to myelin such as the amyloid tracer [ 11 C]PiB or [ 11 C]MeDAS 10,11 or by MRI 12,13 . Unfortunately, histopathology is not applicable for in vivo disease monitoring, myelin tracers are not ideal due to binding to multiple targets and the abundance of myelin, and while structural and diffusion MRI offer some insight into the structural integrity of white matter, MRI measurements are not specific to white matter tissue properties such as myelination or fiber density 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there are many more MRI modalities that are sensitive to myelin largely beyond the scope of this review: For a comprehensive review, please refer the following (Alonso‐Ortiz, Levesque, & Pike, ; Heath, Hurley, Johansen‐Berg, & Sampaio‐Baptista, ; MacKay & Laule, ). However, in a narrower sense, we can include magnetization transfer (MT) imaging and multi‐component relaxation (MCR) time measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a growing interest in assessing the content of intra‐cortical myelin via noninvasive but indirect neuroimaging techniques. While other quantifications of intra‐cortical myelin are under development (Alonso‐Ortiz, Levesque, & Pike, ; Does, ; Heath, Hurley, Johansen‐Berg, & Sampaio‐Baptista, ), previous magnetic resonance imaging (MRI) studies have shown that the ratio between the T1‐ and T2‐weighted MRI signal intensity can provide useful information regarding the neocortical myelo‐architecture (Grydeland et al, ; Rowley et al, ; Shafee, Buckner, & Fischl, ). The T1‐weighted and T2‐weighted signals are the two basic MRI signals which, respectively, relate to the spin–lattice and spin–spin relaxation time (the spin is the intrinsic rotation of protons while the lattice is their surrounding environment).…”
Section: Introductionmentioning
confidence: 99%